Chemical cycles in the biosphere - Stonebarger, Bill; Hawkhill Associates (Wisconsin : Hawkhill Associates Inc., 2004)
Helps students develop a basic understanding of the cycling of chemicals in the earth's biosphere. Shows the good and bad effects chemicals have on our world, as well as the processes through which they produce the effects. Also includes guided questions and mastering quiz
Title from title screen
Videographers, Jane Denny, Michael Stonebarger ; graphics, Lin Haley, Doug Normington, Michael Stonebarger ; editors, Jane Denny, Bill Stonebarger ; music, Michael Stonebarger
Keywords: Biochemistry; Chemicals -- Physiological effect; Biosphere; Pollution -- Environmental aspects; Chemical processes